Zoos as educational and conservation spaces: perspectives from (future) teachers - Wolf, Raya Lyzanne; Dierkes, Paul Wilhelm; Kleespies, Matthias Winfried (Frontiers in Education, 2025)
IntroductionZoological gardens, which are popular destinations for school trips due to their important function as an extracurricular place of learning, also regard themselves as important institutions for environmental protection. However, there are only a limited number of studies that deal with teachers’ attitudes toward zoos. The aim of this study is to investigate how teachers and trainee teachers perceive zoos as an extracurricular learning place.MethodsFor this purpose, 126 teaching students and 303 teachers from Frankfurt participated in a paper or online survey. The survey covered three different topics: emotional attitude toward the zoo, perception of the zoo’s tasks, and perception of the zoo as an extracurricular place of learning. Furthermore, participants were asked about their previous experiences at the zoo. The study examined differences between genders, different age groups, and different teaching professions.ResultsThe results reveal no difference between the genders, but significant differences between age groups, with younger generations having more negative perceptions than older ones. Additionally, teachers from primary schools have a more positive view of the zoo as an extracurricular place of learning compared to those from high schools.DiscussionIt is therefore important to educate future teachers about the opportunities of zoos and the various ways in which they can be integrated into the classroom. In order to achieve this, zoos must establish additional points of contact for secondary schools, such as guided tours or specific teaching materials.